Process-evaluation and outcome-evaluation of a training programme for healthcare professionals in oncology to enhance their competencies in caring for patients with minor children: a study protocol for a randomised controlled pilot study - Laura Inhestern; Wiebke Frerichs; Lene Marie Johannsen; Corinna Bergelt (BMJ Open)
Introduction Patients with cancer having minor children experience particular burden and strains. Being patient and parent at the same time is associated with specific needs of support. Therefore, the communication of child-related and family-related issues plays an important role in patient care. This study aims at testing the feasibility of a training to improve the situation of patients with cancer having minor children and their families by enhancing the competencies of healthcare professionals (HCPs, eg, physicians, nurses, psychologists) in caring for patients with cancer having minor children. Moreover, the study aims at testing the study design and outcomes of the evaluation concept and preliminary effects of the training.Methods and analysis We will conduct a randomised controlled pilot trial with three arms (face-to-face training versus web-based training versus waitlist control group) to investigate the study aims. Primary outcome will be the competency to approach child-related and family-related topics in patients with cancer measured using comprehensive case vignettes. Secondary outcomes will be communication and attitudes regarding child-related and family-related topics and self-efficacy in clinical communication skills. Outcomes will be assessed prior to the training and after the training as well as 3 months after the training. Data will be analysed using descriptive analyses, group comparisons and linear mixed models.Ethics and dissemination The study was approved by the Local Psychological Ethics Committee of the Center for Psychosocial Medicine of the University Medical Center Hamburg-Eppendorf (LPEK-001). At the end of the study, a web-based training and a face-to-face training intervention to enhance the competencies of HCPs in caring for patients with cancer having minor children will have been systematically developed and the study design and evaluation concept will have been evaluated. The results of the study will be disseminated through peer-reviewed journals and conference presentations.Trial registration number DRKS00015794.